Prevalence, Pattern and Effect of Intimate Partner Violence against Women in Abeokuta, South West Nigeria - AbdulMumin Kayode Ahmed; Ayotunde Sherif Azees; Mojirola Martina Fasiku; Olanrewaju Saheed Jimoh; Gloria Bosede Imhonopi; Abiola Oluwatoyin Temitayo-Oboh; Rasheed Abiodun Salam; Ibrahim Ahmed El-Imam; Omobola Yetunde Ojo; Emmanuel Chukwudi Ehiem (Nigerian Postgraduate Medical Journal)
Background: The world over, women are victims of violence in close and intimate relationships where they are expected to be safe and protected. Intimate partner violence (IPV) significantly impacts the physical and mental well-being of those affected. This study assessed the prevalence, pattern and effects of IPV amongst women in Abeokuta South Local Government Area (LGA) of Ogun State, South West Nigeria. Materials and Methods: This community-based cross-sectional study was carried out in Abeokuta – South LGA in Ogun State. Data were collected from 339 women in intimate relationships using a structured interviewer-administered questionnaire. Ethical approval (HPRS/381/471) was obtained from the Ogun State Ministry of Health Ethical Review Committee. Analysis was done using IBM® SPSS version 23, and results were presented in frequencies and proportions using tables and charts. Results: About three-quarters (73.2%) of the 339 respondents had experienced one form of IPV. Psychological/emotional violence, 224 (66.1%), and physical violence, 161 (47.5%), were the study’s most commonly reported forms of violence. Amongst those affected, 186 (54.9%) were ‘insulted’, 87 (25.7%) were ‘embarrassed in public’ and another 124 (36.6%) were slapped. The effects of IPV reported were bruises/lacerations, unwanted pregnancies, sexually transmitted infections and attempted suicide. Conclusion: The prevalence of IPV of all forms were high in the studied population. Therefore, the government needs to create more awareness of the problem and promote investments in women’s empowerment to reverse this trend.